Extraction of antioxidant from kundur plant - Muhammad Bilal, Muslim (2014)
Kundur or its scientific name Benincasa Hispida, is a member of cucurbitaceae family and it is categorized as one of the more famous crops that is grown primarily for its fruits. These plants are usually recognized for their nutritional and medicinal properties. Commonly, the antioxidant from plant has been extracted by conventional extraction such as Soxhlet extraction and includes supercritical carbon dioxide extraction. However, those methods have a lot of disadvantages such as the process need high temperature and low pH which the result may come in acidic condition and the process is difficult to achieve high percentage of yield in the product. Therefore, another type of extraction must be conducted to replace the entire problem mentioned before. So, enzymatic-assisted extraction has been choosing to replace all the conventional extraction method. Mostly, enzymatic extraction gives a lot of advantage compared to conventional extraction such as the process will give more yields in the product.The present study is to investigate the effectiveness of two methods either enzymatic extraction or Soxhlet extraction in obtaining of antioxidants from the Kundur plant. Generally, there are three major parts in completing the researches on extraction of antioxidant from Kundur plant. The first part is the sample preparation. The sample consists of Kundur peels and leaves were grounded into fine powder in order to be used in enzymatic extraction. The second part is the extraction process by using conventional extraction. The conventional extraction that used in our researches is Soxhlet extraction. Firstly, the samples were prepared in the Soxhlet apparatus. The oil were obtained by removal the excess of solvent by using the rotary evaporator. The reading of absorbance was obtained by usingUV–vis spectrophotometer. The third part is the enzymatic extraction. For this part, the phenolic compound has been extracted in order to get the absorbance of the antioxidant inside of the sample. The sample was prepared in different temperature which is in the range from 20◦C to 60◦C and different in time which is from 3 until 10 hours in order to obtain the optimum parameter for the extraction process. The phenolic content of the samples was determined by using UV–vis spectrophotometer. The fourth part is the antioxidant determination. The fruit extract was reacted with 2,2-diphenyl-1-picrylhydrazyl (DPPH) and the absorbance was taken about 515 nm. The results shows that the kundur peels have antioxidant activity inside the sample. The reading of the recorded value of the absorbance shows that the linear range was lower than the standard curve. The standard curve was linear at 25 and 800 μM. These results suggest that it is possible to produce antioxidant from Kundur content, peel and seedand it can expands the usage of Kundur plant and it also can reduce the cost in production of antioxidant in Malaysia.